How Peace was achieved in Byzantium and Medieval Europe - Elena Ene Drăghici-Vasilescu (Athens Journal of History)
Aristophanes2 (446–386 BC), Thucydides (460–c. 400 BC),3 and Erasmus of Rotterdam (1466–1536)4 were concerned with the importance of maintaining peace among peoples and wrote about this concept. The latter author even speaks about the ‘Arts of Peace’ in his third book dedicated to the education of a prince. But recent literature, especially that within the field of Byzantine and European Medieval culture, does not containsubstantial works dedicated to the notion of peace. My main research question is why this is the case since this notion connects many others and should be central to academic research. Within the paper I elaborate on several types of peace agreements: those confirming a ‘complete’ victory of one of the opponent parties involved in a war, those reached mainly by exchange of territories, those having the exchange of prisoners as central, and those referring to the payment of tribute for various purposes.